2012
DOI: 10.1073/pnas.1116972109
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin protein 1 homologue Swi6 acts in concert with Ers1 to regulate RNAi-directed heterochromatin assembly

Abstract: In fission yeast, the RNAi pathway is required for centromeric heterochromatin assembly. siRNAs derived from centromeric transcripts are incorporated into the RNA-induced transcriptional silencing (RITS) complex and direct it to nascent homologous transcripts. The RNA-induced transcriptional silencing-bound nascent transcripts further recruit the RNA-directed RNA polymerase complex (RDRC) to promote dsRNA synthesis and siRNA production. Heterochromatin coated with Swi6/Heterochromain Protein 1 is then formed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 32 publications
5
41
0
Order By: Relevance
“…The Swi6 protein, which binds to methylated H3K9, plays a major role in linking heterochromatic transcription with RNA degradation by promoting the interaction of heterochromatic transcripts with the RNAi and exosome pathways (see Fig. 4, dotted lines) (Motamedi et al 2008;Reyes-Turcu et al 2011;Hayashi et al 2012;Keller et al 2012;Rougemaille et al 2012).…”
Section: Rnai and Heterochromatin Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…The Swi6 protein, which binds to methylated H3K9, plays a major role in linking heterochromatic transcription with RNA degradation by promoting the interaction of heterochromatic transcripts with the RNAi and exosome pathways (see Fig. 4, dotted lines) (Motamedi et al 2008;Reyes-Turcu et al 2011;Hayashi et al 2012;Keller et al 2012;Rougemaille et al 2012).…”
Section: Rnai and Heterochromatin Assemblymentioning
confidence: 99%
“…4A,B) (Motamedi et al 2008). Specifically, Swi6 interacts with an accessory factor called Ers1, which, in turn, interacts with the RDRC complex to promote dsRNA synthesis and RNA degradation (Hayashi et al 2012;Rougemaille et al 2012). In addition, Swi6 has nonspecific affinity for RNA and may help retain heterochromatin-transcribed RNAs on the chromosome until they are degraded by the exosome (Keller et al 2012).…”
Section: Small Rnas Initiate Heterochromatin Assembly In Association mentioning
confidence: 99%
“…Finally, because Ers1, but not Swi6, is required for the recruitment of RITS to chromatin (9), Ers1 likely also plays Swi6-independent roles promoting RNAi. In agreement with this, centromeric silencing triggered by the tethering of Hrr1 can bypass a requirement for Swi6, but not Ers1, indicating that the function of Ers1 is not limited to bridging HP1 to RDRC (23). An additional contact between the histone methylation and RNAi machineries is likely to be provided by the LIM domain protein Stc1.…”
Section: Discussionmentioning
confidence: 55%
“…This view is particularly consistent with our genetic suppression results. In addition, while this work was under review, an independent study by Hayashi et al (23) showed that tethering of Hrr1 to centromeric regions can bypass the requirement for Swi6 in heterochromatin formation, further highlighting a role for HP1 in recruiting RDRC to chromatin. The Ers1-Swi6 interaction documented here also likely explains the previously described role for Swi6 in RNAi and the observation that Swi6 physically associates with centromeric transcripts in vivo (4).…”
Section: Discussionmentioning
confidence: 99%
“…A feed-forward silencing loop is established as chromodomain proteins, including the HP1 homolog, and methyl-transferases are nucleated by RITS complexes, and in turn recruit more methyl-transferases. Concurrently, RNA-directed RNA polymerase complexes (RDRCs) are recruited, thus increasing siRNA production (Hayashi et al, 2012; Rougemaille et al, 2012; Yamanaka et al, 2013). A direct link between chromatin, RNAi and RITS was demonstrated when the CSD of pombe HP1 was shown to interact with several members of the RNAi and RITS machinery via the HP1 binding protein, Ers1 (Rougemaille et al, 2012).…”
Section: Discussionmentioning
confidence: 99%